Simultaneous postprandial deregulation of the orexigenic endocannabinoid anandamide and the anorexigenic peptide YY in obesity - Gatta-Cherifi, B; Matias, I; Vallée, M; Tabarin, A; Marsicano, G; Piazza, P V; Cota, D (International Journal of Obesity, 2012)
Background: The endocannabinoid system is a potential pharmacotherapy target for obesity. However, the role of this system in human food intake regulation is currently unknown. Methods: To test whether circulating endocannabinoids might functionally respond to food intake and verify whether these orexigenic signals are deregulated in obesity alongside with anorexigenic ones, we measured plasma anandamide (AEA), 2-arachidonoylglycerol (2-AG) and peptide YY (PYY) changes in response to a meal in 12 normal-weight and 12 non-diabetic, insulin-resistant obese individuals. Results: Both normal-weight and obese subjects had a significant preprandial AEA peak. Postprandially, AEA levels significantly decreased in normal-weight, whereas no significant changes were observed in obese subjects. Similarly, PYY levels significantly increased in normal-weight subjects only. No meal-related changes were found for 2-AG. Postprandial AEA and PYY changes inversely correlated with waist circumference, and independently explained 20.7 and 21.3% of waist variance. Multiple regression analysis showed that postprandial AEA and PYY changes explained 34% of waist variance, with 8.2% of the variance commonly explained. Conclusion: These findings suggest that AEA might be a physiological meal initiator in humans and furthermore show that postprandially AEA and PYY are concomitantly deregulated in obesity.